Transaction balances of small denomination banknotes: findings from the introduction of ES2 - Nikolaus Bartzsch (Deutsche Bundesbank, 2017)
At the end of 2015, the Deutsche Bundesbank had issued a total net amount of just over exteuro45 billion in exteuro20 banknotes. In statistical terms, each resident living in Germany was therefore issued with around 30 banknotes of this denomination. Up until now, it was not clear how many of these German-issued euro banknotes are actually used for payment purposes. Owing to the introduction of the new Europa series of banknotes on 25 November 2015, it was possible to estimate the volume of exteuro20 banknotes that are held for transaction purposes both in Germany and outside the euro area. The estimation of the volume of exteuro20 banknotes held for domestic transaction purposes (known as the domestic transaction balance) is primarily based on the observed return flows of the old series (ES1) of exteuro20 banknotes received by the Deutsche Bundesbank. The cash balance of exteuro20 banknotes held for domestic transaction purposes was estimated at around exteuro8.5 billion at the end of October 2015. This means that only 19% of the total (net) amount of exteuro20 banknotes issued by the Deutsche Bundesbank up to the end of October 2015 were used for transaction purposes within Germany. The remaining 81% has either migrated abroad, been hoarded or got lost. The results of the analysis are also important as a means of explaining the just over exteuro36 billion worth of ES1 exteuro20 banknotes which are still outstanding in the Deutsche Bundesbank's balance sheet. Given that the cash balance held for domestic transaction purposes has since been almost fully replaced, it is no longer to be expected that ES1 banknotes will flow back to the Deutsche Bundesbank in any sizeable amounts. The volume of German-issued exteuro20 banknotes – officially stemming from banknote shipments by the Deutsche Bundesbank – held for transaction purposes outside the euro area was estimated at just over exteuro3 billion at the end of July 2016 using the biometric method. This estimate represents a lower level for the actual cash balance held for transaction purposes, as it does not incorporate banknote exports resulting from foreign travel and cash amounts sent abroad. It is derived from cumulated shipments of ES2 exteuro20 banknotes up to the end of July 2016 and the value of the ES1 and ES2 exteuro20 notes deposited in July 2016 at the shipment branches. In terms of the Deutsche Bundesbank's cumulated net shipments of exteuro20 banknotes in the amount of around exteuro12 billion at the end of 2015, the estimated cash balance (resulting from shipments) held for transaction purposes outside the euro area accounts for around 28%.
Keywords: C49; E41; E58; 330; euro banknotes; biometric method; foreign demand; transaction balances; hoarding; small denominations; ES2